Harga Saham Sektor Makanan dan Minuman Serentak Naik, Ada Apa? - Ramadhani, Farikhah; Sari, Herlinda Maya Kumala; Prapanca, Detak (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to determine the influence of inflation, interest rates, and company performance on the stock prices of food and beverage sector companies listed on the Indonesia Stock Exchange during the period of 2018-2022. The sample used in this study consists of 65 samples taken using purposive sampling technique. Data were obtained through the investment gallery of the Indonesia Stock Exchange located at Muhammadiyah University Sidoarjo, and processed using E-Views 12 software. Based on the research results, it was found that partially inflation and interest rates do not have a significant effect on stock prices. Meanwhile, the company's performance partially influences stock prices significantly. Thus, it can be concluded that the increase in stock prices in the food and beverage sector influenced by inflation and interest rates is only a prediction; in reality, the increase in stock prices in the food and beverage sector is due to the good performance of the companies.